Mismatch Between What Is Expected and What Actually Occurs Triggers Memory Reconsolidation or Extinction - Pedreira, María Eugenia (Cold Spring Harbor Laboratory Press, 2004)
In previous experiments on contextual memory, we proposed that the unreinforced re-exposure to the learning context (conditioned stimulus, CS) acts as a switch guiding the memory course toward reconsolidation or extinction, depending on reminder duration. This proposal implies that the system computes the total exposure time to the context, from CS onset to CS offset, and therefore, that the reminder presentation must be terminated for the switching mechanism to become operative. Here we investigated to what extent this requirement is necessary, and we explored the relation between diverse phases in the reconsolidation and extinction processes. We used the contextual memory model of the crab Chasmagnathus which involves an association between the learning context (CS) and a visual danger stimulus (unconditioned stimulus, US). Administration of cycloheximide was used to test the lability state of memory at different time points. The results show that two factors, no-reinforcement during the reminder (i.e., CS re-exposure) and CS offset are the necessary conditions for both processes to occur. Regardless of the reminder duration, memory retrieved by unreinforced CS re-exposure emerges intact and consolidated when tested before CS offset, suggesting that neither reconsolidation nor extinction is concomitant with CS re-exposure. Either process could only be triggered once the definitive mismatch between CS and US is confirmed by CS termination without the expected reinforcement.